Chemoradiotherapy with FOLFOX plus cetuximab in locally advanced oesophageal cancer: The GERCOR phase II trial ERaFOX. (March 2016) - Lledo, Gérard; Huguet, Florence; Chibaudel, Benoist; Di Fiore, Frédéric; Mineur, Laurent; Galais, Marie-Pierre; Artru, Pascal; Blondin, Valérie; Dupuis, Olivier; Abdiche, Menouar Samir; Jovenin, Nicolas; Pozet, Astrid; et al.
Abstract: Background: To determine efficacy and toxicity of radiation therapy combined with oxaliplatin, 5-fluorouracil, and folinic acid (FOLFOX) and cetuximab in patients with locally advanced oesophageal cancer. Patients and methods: Patients with stage III oesophageal or gastro-oesophageal junction cancer were enrolled in a Simon's two-stage phase II study. Patients received FOLFOX and weekly cetuximab on week 1–10 with concurrent radiotherapy (50.4 Gy in 30 fractions) on week 5–10. Primary end-point was clinical overall response rate (ORR). An ORR rate of more than 50% was expected. Results: Among the 79 included patients, clinical ORR was 77% with 40% complete responses. Median overall survival and progression-free survival were 21.6 and 11.3 months, respectively. The most common grade III–IV toxicities observed during experimental chemoimmunotherapy followed by chemoradiation included neutropenia (28%), oesophagitis (12%), rash (11%), and allergy (9%). There was one treatment-related death due to oesophagitis with gastrointestinal bleeding. Conclusions: Cetuximab-FOLFOX regimen combined with radiotherapy demonstrated its efficacy and was well tolerated. Unfortunately, these results were not confirmed in two recent phase III studies. Highlights: Radiation therapy with oxaliplatin, 5-fluorouracil, and folinic acid (FOLFOX) and cetuximab provides a 77% clinical response rate. Chemoradiotherapy with concurrent FOLFOX and cetuximab was well tolerated. A high Atkinson's score of dysphagia correlated with poorer survival.